2009
DOI: 10.1002/ijc.24699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel hub genes associated with liver metastasis of gastric cancer

Abstract: Understanding hub genes involved in gastric cancer (GC) metastasis could lead to effective approaches to diagnose and treat cancer metastasis. In this study, 272 differentially expressed genes between synchronous liver metastasis and the paired GC were selected from microarray assays. KEGG pathway analysis indicated that of 13 enriched pathways, 8 were involved in cancer metastasis. Literature-based annotations showed that the differentially expressed genes significantly enriched known metastasisrelated genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 46 publications
0
54
2
Order By: Relevance
“…This was consistent with our previous finding. 15 Immunohistochemistry of the 28 paired FFPE specimens indicated that the ratio of positive NR4A2 immunostaining in adjacent mucosa was 64.3% in lymphocyte nuclei, 39.3% in epithelial cytoplasm, and 25.0% in epithelial nuclei; the ratio in tumors was 14.3% in lymphocyte nuclei, 0% in cancer cytoplasm, and 53.6% in cancer cell nuclei.…”
Section: Expression Pattern Of Nr4a2 In Gcs and Adjacent Mucosamentioning
confidence: 98%
See 3 more Smart Citations
“…This was consistent with our previous finding. 15 Immunohistochemistry of the 28 paired FFPE specimens indicated that the ratio of positive NR4A2 immunostaining in adjacent mucosa was 64.3% in lymphocyte nuclei, 39.3% in epithelial cytoplasm, and 25.0% in epithelial nuclei; the ratio in tumors was 14.3% in lymphocyte nuclei, 0% in cancer cytoplasm, and 53.6% in cancer cell nuclei.…”
Section: Expression Pattern Of Nr4a2 In Gcs and Adjacent Mucosamentioning
confidence: 98%
“…Cell invasive ability and anchorageindependent growth of the transfected cells were examined as described. 21 Real-Time Quantitative Reverse-Transcription PCR and Western Blot Total RNA was isolated and subjected for quantitative real-time reverse-transcription polymerase chain reaction (qRT-PCR) as described, 15 and primers for NR4A2 were described. 15 …”
Section: Nr4a2 Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrating PPI networks with expression data, for example, led to the identification of cancer susceptibility genes and oncogenes in breast carcinomas [122], B-cell acute myeloid lymphomas [123,124]; the identification of markers for metastasis in breast [125,126], colorectal [127,128] and gastric [129] cancer; the prediction of disease outcome [130] and response to chemotherapy [131,132] and the determination of therapy-resistance genes [133,134]. By combining protein-protein and protein-DNA interaction studies Kim et al identified a Myc-centered regulatory network in embryonic stem cells, and showed that the Myc module is active in various cancers and predicts cancer outcome [135].…”
Section: Disease Disease Gene or Pathway Referencementioning
confidence: 99%